Digital Technology Literacy, And Digital Economy Literacy as an Effort to Improve Business Sustainability In Banten's Micro And Small Industries In The Era Of Business Uncertainty - Sutisna; Syamsul Hidayat; Naufal Affandi; Mamay Komarudin; Pratama (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Digital technology is beneficial in running a business in production, marketing, and finance. However, not all business actors have used digital technology and the digital economy to help run their businesses, especially micro and small business actors. This study aims to investigate the role of digital technology literacy and the digital economy in encouraging the interest of micro and small business actors to use digital technology that will drive the sustainability of their businesses. The survey was conducted on 162 micro and small business actors in Banten province. This study uses the technology acceptance model (TAM) theoretical framework. In this research, data analysis using SEM-PLS. The study results show that digital technology and economic literacy significantly affect perceived Ease of use and usefulness. Digital technology literacy has an effect on business sustainability, but digital economic literacy has no effect. Perceived Ease of use and perceived usefulness significantly affect the intention to use. Intention to use has a significant effect on business sustainability. This research also strengthens the role of TAM as a mediating variable for business sustainability variables. This research provides scientific insights in the field of digital technology and business sustainability, as well as provides practical insights for business actors and the government.